Velocity‐free coordinated attitude synchronisation and tracking control of multiple spacecraft. Issue 3 (1st February 2020) - Liu, Xiaoping; Zou, Yao; Meng, Ziyang; You, Zheng
Abstract : This study investigates the coordinated attitude synchronisation and tracking problems of multiple spacecraft without angular velocity measurements. The spacecraft attitudes are represented by modified Rodrigues parameters. First, for the attitude synchronisation problem, a distributed control algorithm with local information interaction is developed by introducing two auxiliary systems to address the velocity‐free problem. Next, for the attitude tracking problem, the authors first design a non‐linear distributed observer for each follower spacecraft such that the leader reference information can be estimated accurately. By treating this estimation information as a reference, a tracking control with the help of an auxiliary system is then developed for the attitude tracking without using angular velocity measurements. For both cases, the asymptotic stability of the overall closed‐loop systems is proven in terms of Lyapunov theory. Finally, numerical examples are given to validate the effectiveness of the proposed distributed control algorithms.